Reduced cell proliferation and promotion of apoptosis by Leu5AMD in osteosarcoma cells - Wu, Xiaofeng; Zhou, Zihui (Archives of Biological Sciences, 2017)
Leu5AMD is an actinomycin D (AMD) analog obtained by replacing both N-methylvalines present in AMD with N-methylleucines. The potential of Leu5AMD for the treatment of osteosarcoma cells and its mechanism of action are not clearly understood. In this study, we examined the potential use of Leu5AMD in halting the proliferation of the human osteosarcoma cell line Saos-2. Saos-2 cells were treated with different concentrations of Leu5AMD, and proliferation, cell viability, apoptosis and the cell cycle were examined. Among the various concentrations used, 1.2 μM and 6 μM Leu5AMD exhibited a significant effect on Saos-2 cells compared with untreated cells. The proliferation assay and Hoechst staining indicated that Leu5AMD treatment of Saos-2 human osteosarcoma cells resulted in a significant reduction in cell proliferation and enhanced apoptosis. Western blot analysis revealed that Leu5AMD-treated cells had significantly reduced cyclin expression compared with the control. Leu5AMD is responsible for inducing cell cycle arrest and apoptosis. These results support the development of a new drug for the treatment of osteosarcoma. https://doi.org/10.2298/ABS160712001W Received: July 12, 2016; Revised: December 2, 2016; Accepted: December 2, 2016; Published online: August 9, 2017 How to cite this article: Wu X, Zhou Z. Reduced cell proliferation and promotion of apoptosis by Leu5AMD in osteosarcoma cells. Arch Biol Sci. 2017;69(4):577-83.